Slovenia dossier archive - Košir, Matevž (Atlanti +, 2025)
Purpose: The goal is to explore how political factors shaped the way archives in Slovenia were organized and operated throughout the 20th century.Method: The author employed a qualitative, historical-analytical method, draw-ing on archival records, historical literature, and archival theory to explore the intersection of politics and archival development in Slovenia.Results: The history of archives in Slovenia is not only a story of institutions and documents but also a multifaceted narrative of power, memory, vision, and societal evolution.Conclusions: The review of the history of Slovenian archives confirms the great importance of archival principles, particularly in connection with the Universal Declaration on Archives (2010). It highlights how adherence to these principles must guide the development, organization, and accessibility of archival institu-tions also in Slovenia, ensuring the preservation of documentary heritage and the promotion of transparency, accountability, and the right to information.
Keywords: Arhivi; arhivska mreža; arhivska služba; Politika in vladanje; Socializem